2021
DOI: 10.24815/jpsi.v9i3.20829
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Problem Based Learning Model on Creative and Critical Thinking Skills in Static Fluid Topics

Abstract: Creative and critical thinking skills are one of the demands of new skills needed by students in the current era. One of the learning models that can sharpen creative and critical thinking skills is Problem based learning (PBL). Heretofore, research related to creative and critical thinking skills with PBL in understanding static fluid material is still minimal. Therefore, this research explored it. This study aimed to analyze the effect of PBL on students' creative and critical thinking skills. This type of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…This learning activity can help students to improve their critical thinking skill for problem solving materials. In general, creative thinking is correlated with critical thinking and problem solving skills (Wenno & Batlolona, 2021).…”
Section: ) Interaction Of Learning Models With Problem Solving Skills...mentioning
confidence: 99%
See 1 more Smart Citation
“…This learning activity can help students to improve their critical thinking skill for problem solving materials. In general, creative thinking is correlated with critical thinking and problem solving skills (Wenno & Batlolona, 2021).…”
Section: ) Interaction Of Learning Models With Problem Solving Skills...mentioning
confidence: 99%
“…In addition, the learning carried out based on the the student worksheet followed the SSCS dan PQ4R syntax. Students are more focused on determining the problems sought throught experiments and understanding physics concepts throught actual experiments (Wenno & Batlolona, 2021). 7) Interaction between learning models, critical thinking, and problem solving skills on learning outcomes…”
Section: ) Interaction Between Critical Thinking and Problem Solving ...mentioning
confidence: 99%
“…Students engage in a learning process that demands critical thinking, collaboration with team members, information gathering, and exploration of different possibilities to solve problems. Several studies that have been conducted show that PBL can improve students' conceptual understanding [9], critical thinking skills [16], creative thinking skills [17], and science process skills [18]. PBL significantly impacts students' learning outcomes compared to conventional learning models [19].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last half century, teachers have shown that PBL can be used effectively to improve cognitive and emotional skills in learning (Dolmans et al, 2016;Suparman et al, 2021;Wenno et al, 2021). Some researchers suggest that technology-based PBL has a greater impact on cognitive and emotional abilities than traditional or face-to-face PBLs (Ismail et al, 2018;Phungsuk et al, 2017).…”
Section: Introductionmentioning
confidence: 99%